1998
DOI: 10.1002/(sici)1097-0215(19980619)79:3<245::aid-ijc6>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the smooth muscle calponin gene in human osteosarcoma and its possible association with prognosis

Abstract: The basic calponin gene is a smooth muscle differentiation‐specific gene that encodes an actin‐binding protein involved in the regulation of smooth muscle contractility. We studied the expression of the calponin gene in 8 human osteosarcoma cell lines and 17 primary human osteosarcoma tissues by RT‐PCR analysis. We also analyzed mRNA expression of smooth muscle‐specific genes including SM22α, caldesmon and α‐actin, and for neutral and acidic calponin isoforms. The genes were expressed at various levels by oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Also, h1-calponin knockout mice displayed enhanced ectopic bone formation when they were stimulated by recombinant human bone morphogenetic protein-2, once again suggesting calponin's function as a suppressor of cell proliferation. Calponin has been detected in the cytoplasm of human osteosarcoma cells, and the survival rate of patients whose tumors exhibit calponin is significantly higher than that of those whose tumors do not express calponin (50). Consistently, the h1-calponin knockout mice also had an early onset of cartilage formation and ossification and accelerated healing of bone fractures (51).…”
Section: Discussionmentioning
confidence: 86%
“…Also, h1-calponin knockout mice displayed enhanced ectopic bone formation when they were stimulated by recombinant human bone morphogenetic protein-2, once again suggesting calponin's function as a suppressor of cell proliferation. Calponin has been detected in the cytoplasm of human osteosarcoma cells, and the survival rate of patients whose tumors exhibit calponin is significantly higher than that of those whose tumors do not express calponin (50). Consistently, the h1-calponin knockout mice also had an early onset of cartilage formation and ossification and accelerated healing of bone fractures (51).…”
Section: Discussionmentioning
confidence: 86%
“…The resulting cDNA was amplified by PCR using CALD1 specific primer sets spanning the splice sites of this gene toward all of the four splicing variants of l-CaD as described elsewhere. 7 A primer set for the CALD1, designed to amplify all of the splicing variants, 25 was used for initial examining the microdissected samples (the product size for l-CaD isoforms is 744 bp). Glyceraldehyde 3-phosphate dehydrogenase (GAPD) fragment 26 was prepared by PCR as an internal control.…”
Section: Cald1 Transcript Analysismentioning
confidence: 99%
“…The effect of this mutation on the contractile function of smooth muscle is reported elsewhere . Since basic calponin is expressed at various levels in human osteoblast cell lines and osteosarcoma tissues (Yamamura et al 1998), we examined whether the endogenous murine basic calponin is expressed in bone tissues. Reverse transcription-PCR (RT-PCR) analysis using total RNA prepared from the calvaria bone tissue of wild-type mice demonstrated that the endogenous basic calponin messenger RNA (mRNA) was highly expressed in embryos, expressed at low levels until 7 weeks after birth, and was not at all detectable in 12-week-old mice ( Fig.…”
Section: Targeting Of the Basic Calponin Gene And Its Endogenous Expmentioning
confidence: 99%